Kubernetes Microservices with Docker - Vohra, Deepak (Apress : Imprint: Apress, 2016)
The book is about Kubernetes, a container cluster manager.  The book discusses all aspects of using Kubernetes in applications. Starting with installing Kubernetes on a single node, the book introduces Kubernetes with a simple Hello example and discusses using environment variables in Kubernetes. Next, the book discusses using Kubernetes with all major groups of technologies such as relational databases, NoSQL databases, and in the Apache Hadoop ecosystem.  The book concludes with using multi container Pods and installing Kubernetes on a multi node cluster. No other book on using Kubernetes - beyond simple introduction - is available in the market.  Specifically, you'll learn the following: How to install Kubernetes on a single node How to install Kubernetes on a multi-node cluster How to set environment variables How to create a multi-container pod How to use volumes How to use Kubernetes with Apache Hadoop Ecosystem How to use Kubernetes with NoSQL Databases How to use Kubernetes with RDBMS.